Persistence of Trichoderma species within maize stem against Fusarium verticillioides - Sobowale, A.A.; Cardwell, K.F.; Odebode, A.C.; Bandyopadhyay, Ranajit; Jonathan, S.G. (Informa UK Limited, 2007)
The ability of four Trichoderma isolates to colonize maize stem and persist therein in presence of Fusarium verticillioides were tested in the field. These were three strains of Trichoderma pseudokoningii and one strainof T. harzianum. There were three pairing methods based on the commonly used toothpick inoculation method. This ensures direct introduction of pathogen and antagonist using toothpicks dressed separately with pathogen and antagonists. Maize stems were inoculated with antagonist alone, pathogen alone and sterile toothpicks erved as controls. The proportion of antagonist recovered was plotted against distance moved within maize stem. All Trichoderma isolates had endophytic growth within the maize stem in all pairing methods, giving a significant quadratic response with distance from the inoculation point. Recoveries of antagonists were slightly more in lower than upper internodes. Simultaneous inoculation of pathogen and antagonist gave the best endophytic growth of antagonists. T. harzianum strain 2 and T. pseudokoningii strain 4 had the best endophytic growth in all pairing methods. The pathogen had no effect on endophytic growth of T. pseudokoningii strain 4. T. pseudokoningii strain 4 and T. harzianum strain 2 improved in endophytic growth in the presence of pathogen. Competitive exclusion of F. verticillioides from maize plant using endophytic Trichoderma spp. could be a possibility.